Analisis Net Profit Margin, Total Assets Turn Over dan Equity Multiplier dengan Metode Common Size terhadap Upaya Meningkatakan Kemampulabaan. Studi Kasus Pada PT (Persero) Angkasa Pura II - Pardede, Robert Pius; Triandi, Triandi; Febrianti, Egi (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2006)
The purpose of this research is to find out the influence of net profit margin, total assets turn over, and equity multiplier to profitability. The result of research showed that finance performance of Angkasa Pura II Ltd. has not been efficient yet. Therefore, the management has need of working hard in order to be able to defend companyâs ability of getting profit. The management must be aware at the increase or decrease of variables that has formed ability of profit or ROE. If one of variables comes to decrease, the management has to make the effort to increase other variables. When net profit margin decreases, the company has to make the effort to increase the value of total asset turn over by increasing the value of equity multiplier by decreasing leverage from the outside and maximizing self-funding for operational activities of the company. Keywords: Net Profit Margin, Total Asset Turn Over, Equity Multiplier, Profitability